Using Data to Inform Decision-Making: A Focus on Department & Program Enrollments - Craig D Hlavac (Academic Chairpersons Conference Proceedings, 2022)
Department chairs are frequently required to make decisions on behalf of their department. Most significant decisions require input from department stakeholders (e.g. faculty, staff, students) yet the responsibility for guiding this process – including gathering and presenting relevant data – generally resides with the chairperson. Determining what data is needed for each situation can be challenging, especially when considering enrollments. This session will provide current and prospective chairpersons with practical suggestions for seeking relevant data points to assess and guide department initiatives with a specific focus on enrollments. Simple, measurable recruitment and retention strategies will also be discussed. Participants will have opportunities to share experiences and collectively develop strategies for immediate consideration. Institutional teams are especially encouraged to attend.
Keywords: Data; enrollments; decision-making; strategic planning; data trends